1994
DOI: 10.1111/j.1440-1827.1994.tb01684.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial chondromyxoid fibroma extending into the jugular foramen

Abstract: A case is reported of an intracranial chondromyxoid fibroma (CMF) in a 67 year old man. The tumor originated in the petrous part of the temporal bone and extended into the jugular foramen. Microscopically, the tumor showed a lobular appearance, and was composed of spindle or stellate cells in an abundant myxoid, chondroid stroma. Immunohistochemically, S-100 protein was positive in the tumor cells and myxoid stroma. Intracranial CMF, especially in an elderly person, is exceedingly rare. Clinical and pathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Indeed, only one chondromyxoid fibroma reported in the literature has caused facial paralysis and was not localized to the mastoid. 8 Radiographically, the tumors in this series did not demonstrate the classic findings of chondrosarcoma, including bony scalloping, contrast enhancement, or matrix calcification seen commonly on CT imaging. 3 On MRI, there is typically T1 hypointensity, T2 hyperintensity, and postcontrast enhancement.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Indeed, only one chondromyxoid fibroma reported in the literature has caused facial paralysis and was not localized to the mastoid. 8 Radiographically, the tumors in this series did not demonstrate the classic findings of chondrosarcoma, including bony scalloping, contrast enhancement, or matrix calcification seen commonly on CT imaging. 3 On MRI, there is typically T1 hypointensity, T2 hyperintensity, and postcontrast enhancement.…”
Section: Discussionmentioning
confidence: 52%
“…Considering reports on chondrogenic tumors of the temporal bone, petrous apex chondrosarcoma appears to be much more likely to present with cranial nerve dysfunction. Indeed, only one chondromyxoid fibroma reported in the literature has caused facial paralysis and was not localized to the mastoid …”
Section: Discussionmentioning
confidence: 99%
“… 8 15 Though not always present, the characteristic features of CMF include lobular appearance, chondromyxoid stroma, and fibrous tissue with multinucleated giant cells. 16 Nielsen et al performed ultrastructural examination on six tumor samples finding populations of cells with features of three different cell types: chondrocytes, myofibroblasts, and a mixture of both chondrocytes and myofibroblasts. 17 It should be noted that if the lesion shows significant atypia or mitotic activity, the diagnosis of CMF should be reconsidered.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial CMF is a rare clinico‐pathological entity and about 34 cases (including this study) have been reported (Table 1). The sites of occurrences for the reported cases are: four cases from occipital bones, 4,6 , 7 eight cases from frontal bones, 5,7–11 five cases from sphenoid bones, 7,12 , 13 one case from petrous‐sphenoid junction, 14 one case from mastoid with extension into occipital bone, 15 three cases from temporal bones, 16–18 one case from nasal bone with involvement of frontal and ethmoid sinuses, 19 three cases from clivus with involvement of frontal and ethmoid sinuses, 20 one case from mastoid and temporal bone, 21 one case from ethmoid sinus, 7 one case from anterior fossa, 22 one case from middle and posterior fossa 23 and two cases from parietal bones 24 (this study). Two other cases were reported simply as involving calvarium 7 and skull base 25 .…”
Section: Discussionmentioning
confidence: 99%